The seated-single-arm-row as a post-activation potentiation exercise to enhance power output during kayaking on an ergometer - Lee, M. J.C.; Yong, G.; Vinh-Tan, N. (ISBS Proceedings Archive (Michigan), 2022)
This study investigated if the seated-single-arm-row (SSAR) could be used as a post-activation-potentiation-exercise (PAPE) during warm up to induce enhanced power output during kayaking on an ergometer. Ten well-trained kayakers (4 females, 6 males) performed three repetitions of the SSAR at 91% one-repetition maximum as the PAPE. Participants were assessed for their peak and average power output while performing 14 maximal effort strokes on a kayak ergometer; to simulate a race start; with versus without PAPE as a warm up, at three-minute intervals up to 18 minutes. Mean peak power with PAPE was found to be approximately 6% higher (1172.5 vs 1106.8 W) compared with no PAPE, t(9)=2.61, p=0.03. No differences in mean average power were found. Six out of the 10 kayakers registered higher mean peak and average power in one of their experimental trials compared with their control trial. These kayakers could be positive responders to PAPE. The SSAR performed during warm up enabled kayakers to increase their peak power output when paddling on an ergometer, but did not result in higher average power output. The utility of the SSAR as a PAPE to enhance overall power output when paddling on an ergometer, with the perspective of applying this technique to enhance performance during on-water kayaking, requires further investigation.